Defining Legal Contours of Digital Identity Theft - Tantimin, Tantimin; Febriyani, Emiliya; Agustianto, Agustianto; Hutauruk, Rufinus Hotmaulana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The proliferation of digital technology has challenged the traditional understanding of identity and subsequently brings forth its own unique legal implications. Identity theft as a crime that has existed even before this development has also brought its own unique legal implications, particularly in the realm of criminal law. Using normative legal research method, this research aims to establish the boundaries around digital identity theft, to distinguish it from the traditional identity theft, to provide a more relevant and robust understanding of its criminality within the digital age. Results of this study highlight the gaps in Indonesia's current legal framework, emphasizing the need for a revised approach that distinctly addresses the complexities of digital identity theft. The research proposes a model of normative development aimed at refining legal definitions and enhancing enforcement mechanisms to better combat this modern crime. This model seeks to provide a more relevant and robust legal framework, ensuring that the legal system is responsive and adaptive to the challenges posed by digital advancements.